THE ARTICLE IS DEDICATED TO THE TEACHING METHODOLOGY OF USING THE SYSTEM OF THE MEANS OF THE FOLK ART IN FANNING ART CULTURE OF THE STUDENTS - H.A. Bohatyrova (Academy of Cognitive and Natural Sciences, 2022)
The article is dedicated to the teaching methodology of using the system of the means o f the folk art in fanning art culture of the students. The ways of the intensification of the teaching and upbringing process of the readiness of the teachers-to be o f Handicraft during studying o f the disciplines o f Art are led to made conditional